Beyond Huntington’s disease - late-onset chorea caused by a homozygous variant in ERCC4 - Barthel, Paula Charlotte; Popa, Bertrand; Ebert, Anne; Mohamed, Sherif A.; Weishaupt, Jochen H.; Conrad, Julian (The cerebellum, 2025)
Genetic alterations in the ERCC4 gene typically cause Xeroderma pigmentosum and other nucleotide excision repair disorders. Neurologic symptoms are present in some of these patients. In rare cases, ERCC4-mutations can manifest with prominent neurologic symptoms. We report a 62-year-old woman who presented with a movement disorder caused by a homozygous pathogenic variant in the ERCC4 gene. She presented with a hyperkinetic movement disorder (chorea) that affected the distal limbs as well as facial muscles and jaw. There was no ataxia. Extensive clinical evaluation revealed predominantly fronto-parietal and cerebellar atrophy on brain MRI with sparing of the basal ganglia and mesial temporal lobe. Iron and sparse Ca2+ deposits were found in the basal ganglia. The detailed neuropsychological evaluation revealed deficits indicating subcortical-prefrontal, subcortical-parietal and frontotemporal dysfunction, without significant impairments in activities of daily living. The audiogram revealed mild age-related hearing impairment, electroneurography was unremarkable without signs of polyneuropathy. The dermatologic examination showed no signs of skin cancer. Knowledge about ERCC4-related neurodegeneration is limited and the disease is likely underdiagnosed. Nucleotide Excision Repair Disorder-related neurodegeneration should be considered as a differential diagnosis in patients with adult-onset neurodegenerative disorders, even if dermatologic complications are absent and the family history is negative. The preserved caudate volume in our ERCC4 patient could be a hint towards this rare condition. Treatment is symptomatic. Once the diagnosis is established, patients need to be advised to have regular medical consultations to prevent disease complications such as skin cancer.